2023
DOI: 10.3390/f14091716
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Factors Jointly Lead to the Lower Soil Microbial Carbon Use Efficiency of Abies fanjingshanensis in a Typical Subtropical Forest in Southwest China

Xianliang Wu,
Zhenming Zhang,
Jiachun Zhang
et al.

Abstract: Abies fanjingshanensis trees are the only remaining Abies species in a type of subtropical forest of southwest China and are in imminent danger. Previous studies suggested that the massive death of Abies was caused by the unbalanced chemometrics and nutrients in the soil. To the best of our knowledge, for the first time, we evaluated the microbial carbon use efficiency (CUE) in the rhizospheric topsoil and subsoil of A. fanjingshanensis, at high elevation, middle elevation, and low elevation as well as investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…and peanut from the perspective of intercropping between foresters and farmers, and the results showed that loquat yields and soil properties were significantly improved, while emissions of carbon monoxide, methane, and other gases were significantly reduced. Wu et al [24] analyzed the microbial environment in the topsoil and subsoil of root nodules of the endangered species Abies fanjingshanensis using a fungal and bacterial symbiotic network method, indicating that the soil microbial carbon sequestration function in forest environments is an important characteristic of plant growth and development. The important reason for the death of Abies fanjingshanensis is the decrease in microbial carbon use efficiency (CUE).…”
Section: By Studying the Response Relationship Between The Forest Wat...mentioning
confidence: 99%
“…and peanut from the perspective of intercropping between foresters and farmers, and the results showed that loquat yields and soil properties were significantly improved, while emissions of carbon monoxide, methane, and other gases were significantly reduced. Wu et al [24] analyzed the microbial environment in the topsoil and subsoil of root nodules of the endangered species Abies fanjingshanensis using a fungal and bacterial symbiotic network method, indicating that the soil microbial carbon sequestration function in forest environments is an important characteristic of plant growth and development. The important reason for the death of Abies fanjingshanensis is the decrease in microbial carbon use efficiency (CUE).…”
Section: By Studying the Response Relationship Between The Forest Wat...mentioning
confidence: 99%